32.H. Round table: Emergency preparedness: Core competencies for medical students as part of public health workforce. (30th September 2020) - ,; ,
Abstract: The duties encompassed within public health, according to Acheson's definition, are to be undertaken by society as a whole. This is further emphasised within 'ASPHER's European List of Core Competencies for the Public Health Professional' which mentions that public health responsibilities fall upon the 'public health workforce'. If even those outside the medical profession are considered part of the public health workforce, why are medical students being overlooked as a group who can contribute? As representatives of the future generation of medical professionals, shouldn't they be an obvious starting point for practising public health advocacy? Medical students have the potential to act and, with better integration into the public health workforce, could become an asset. Despite them having a legal obligation to contribute in emergency situations, there are insufficiencies or a lack of clarity within the guidelines to highlight and elaborate on what students are specifically expected to be able to carry out in various situations. This is in stark contrast to the predefined lists of competencies against which medical professionals are assessed. This workshop will focus on identifying the core competencies regarding medical students in their contribution to emergency preparedness and how these could be integrated into the existing framework for effecting a structured and organised response. The primary outcome is to achieve better advocacy for public health in future medical professionals with a focus on preparedness for emergency situations. To begin with, research carried out to elucidate whether different countries have set guidelines or competencies that are expected of medical students by the conclusion of their medical studies will be presented. Such guidelines both on national and regional levels were identified and then compared following analysis. This will be followed by more personal accounts from medical students and a discussion of the potential steps that could be introduced to improve emergency preparedness. Shortcomings of such guidelines concerning medical student competencies are further highlighted in times of crisis such as the ongoing COVID-19 pandemic. It is during this time when healthcare systems are stretched and their contribution may be most valuable. The nature of this contribution within the context of international pandemic plans will be explored and debated. Finally this workshop will conclude by opening up the floor for discussion between the panellists and the audience regarding the topics and issues raised. This workshop aims to highlight the need for core competencies in medical education and bring this topic to the forefront for further discussion and analysis amongst professionals, with the eventual international unification, simplification and clarification of these being the ultimate goal. This could be pivotal for the future of public health and in the advancement and evolution of education. Key messages: Armed with suitable competencies, medical students can be an asset to the public health workforce if utilised effectively and in doing so can enhance preparedness response. This project's outcomes are in alignment with ASPHER's European Public Health Core Competencies Programme (EPHCCP) and the WHO Coalition of Partners (CoP).